Sandstone powder activity excitation diagenesis agent prepared by wet method and application of sandstone powder activity excitation diagenesis agent in preparation of recycled aggregate

By using active stimulating diagenetic agents to treat stone powder in the wet sand production process, the problem of degradation of concrete performance during reuse of stone powder is solved, and efficient regeneration and utilization of stone powder and improvement of regenerated aggregate performance is achieved.

CN119430842AActive Publication Date: 2025-02-14RAILWAY CONSTR RES INST OF CHINA ACAD OF RAILWAY SCI CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411333411.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

In the prior art, when the stone powder produced in the wet machine sand production process is reused, it is easy to lead to a decrease in concrete performance and a lack of an effective recycling and utilization technology system.

Method used

A wet method of sand and gravel powder active excitation diagenetic agent, including flocculant degradation components, surfactant components and inorganic cementing components of stone powder, is prepared by flocculation precipitation, ultrasonic stirring flocculation, addition of diagenetic agent and electromagnetic wave energy directional excitation, Regenerated aggregates of a certain strength are obtained by screening and regenerated aggregates of different particle sizes.

Benefits of technology

It realizes efficient recycling and utilization of stone powder, improves the economic benefits of machined sand production, and the performance of the prepared recycled aggregate is the same as that of machined aggregate, and the robustness and crushing indicators meet high standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430842A_ABST
    Figure CN119430842A_ABST
Patent Text Reader

Abstract

The invention discloses a wet-process sandstone powder activity excitation diagenesis agent and application thereof in preparation of recycled aggregate. The stone powder activity excitation diagenesis agent comprises 5-10 parts by mass of a flocculant degradation component, 1-3 parts by mass of a surface active component and 15-20 parts by mass of a stone powder inorganic cementing component, the flocculating agent degradation component is a NaOH or KOH solution with the molar concentration of 2 mol / L to 5 mol / L; the surface active component is lauryl sodium sulfate or octylphenol polyoxyethylene ether with the molar concentration of 0.01 mol / L to 0.1 mol / L; the stone powder inorganic cementing component is a solution prepared from sodium silicate with the modulus being 1.0-1.5, superfine slag powder with the specific surface area being larger than or equal to 600 m < 2 > / kg, the activity index being larger than or equal to 120% and the fineness D90 being smaller than 10 microns and water according to the mass ratio of (3-5): (0.5-1): (8-10). The rock forming agent is utilized to fully excite the activity of the stone powder, the stone powder is used as a cementing material to prepare the recycled aggregate, the particle morphology of the recycled aggregate is more excellent than that of traditional machine-made aggregate due to the fact that the stone powder is coagulated, hardened and formed in the agglomeration process, the firmness of the recycled aggregate is smaller than or equal to 8.0%, and the single-stage maximum crushing index is smaller than or equal to 25%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an active diagenetic agent for wet-process sand and stone powder production and application thereof in preparing recycled aggregate. Background Art

[0002] The production process of machine-made sand is mainly divided into dry process and wet process. At present, there is no reasonable and unified recycling technology system for the stone powder produced in the wet machine-made sand production process. The stone powder produced in the wet machine-made sand production process is often collected by repeated washing and drying. The patent "High-efficiency Recovery Process of Ultrafine Particles of Circulating Water for Wet Machine-made Sand (CN 117088562A)" obtains clean fine sand and stone powder particles through repeated washing and precipitation recovery. The patent "A Method for Recycling Waste Stone Powder in a Wet Sand and Gravel Production System (CN 102430467 A)" targets the waste stone powder produced in the wet machine-made sand production process, and re-rinses and dries it and then adds it to the machine-made aggregate to achieve the recycling of the waste stone powder. However, directly adding it to the machine-made aggregate after washing and drying is likely to reduce the performance of the concrete prepared with it.

[0003] The main reason for the poor performance of stone powder utilization in existing inventions and research is that stone powder is only used as a filler to prepare aggregate or concrete, and excessive stone powder without reaction activity is equivalent to artificially introducing defects, resulting in the aggregate or concrete prepared by stone powder having significantly lower performance than conventional materials.

[0004] Therefore, how to use wet sand and gravel powder to prepare recycled aggregate for concrete that meets performance requirements is an urgent problem that technicians in this field need to solve. Summary of the invention

[0005] In view of this, the present invention provides a wet-process sand and stone powder activation diagenetic agent and its application in preparing recycled aggregate. The stone powder recycled aggregate prepared by the present invention realizes the efficient recycling of wet-process machine-made sand and stone powder, and improves the economic benefits of machine-made sand production.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A wet-process sand and stone powder active diagenetic agent, comprising 5-10 parts by weight of a flocculant degradation component, 1-3 parts by weight of a surfactant component, and 15-20 parts by weight of a stone powder inorganic cementing component;

[0008] The flocculant degradation component is a NaOH or KOH solution with a molar concentration of 2 mol / L to 5 mol / L;

[0009] The surface active component is sodium dodecyl sulfate or octylphenol polyoxyethylene ether with a molar concentration of 0.01 mol / L to 0.1 mol / L;

[0010] The stone powder inorganic cementing component is a solution prepared by mixing sodium silicate with a modulus of 1.0 to 1.5, ultrafine slag powder with a specific surface area of ​​≥600m2 / kg, an activity index of ≥120%, and a fineness D90 of less than 10μm with water in a mass ratio of (3 to 5): (0.5 to 1): (8 to 10).

[0011] The invention discloses an application of an active diagenetic agent for wet-process sand and stone powder production in the preparation of recycled aggregates by wet-process sand and stone powder production.

[0012] A method for preparing recycled aggregate by wet sand and stone powder production, specifically comprising the following steps:

[0013] Step 1: Add a degradable lignin-based water-soluble flocculant to the stone powder slurry produced by wet sand making for flocculation and precipitation, and drain the upper clear water after the precipitation is complete;

[0014] Step 2: Using an ultrasonic stirring and flocculation device to perform ultrasonic stirring and flocculation on the stone powder obtained by wet sand making, so as to accelerate the coagulation of the stone powder under the action of a degradable lignin-based water-soluble polymer flocculant;

[0015] Step 3: adding a stone powder activity activating diagenetic agent to the flocculated stone powder to prepare a primary formed recycled aggregate with a certain strength;

[0016] Step 4: Filter the initially formed recycled aggregate from the diagenetic agent, use the electromagnetic wave energy directional excitation device again to accelerate the hardening of the aggregate, and obtain recycled aggregates of different particle sizes after screening.

[0017] Preferably, the degradable lignin-based water-soluble flocculant is prepared by grafting lignin oligomers with D-lysine through Mannich reaction. The charge neutralization and molecular bridging mechanism of the degradable lignin-based water-soluble polymer is used to promote the flocculation and precipitation of stone powder particles, replacing traditional inorganic polymer flocculants.

[0018] Preferably, the stirring time of ultrasonic stirring flocculation in step 2 is 30s-60s, and the ultrasonic stirring power is 1000W-1500W.

[0019] Preferably, in step three, a diagenetic agent accounting for 5%-10% of the total amount of stone powder is added.

[0020] Preferably, the electromagnetic wave energy directional excitation working parameters in step four; the screening uses a high-frequency vibration screening device to screen the hardened recycled aggregate into recycled aggregates with different particle sizes of 0.15mm~0.30mm, 0.30mm~0.60mm, 0.60mm~1.18mm, 1.18mm~2.36mm, 2.36mm~4.75mm, 5.00mm~10.00mm and 10.00mm~20.00mm.

[0021] Preferably, the device for preparing recycled aggregate by wet-process sand and stone powder comprises: a stone powder flocculation and sedimentation device, an ultrasonic stirring flocculation device, a vacuum adsorption and filtration device, an electromagnetic wave energy directional excitation device and a high-frequency vibration screening device.

[0022] The stone powder flocculation and precipitation device is used to put the degradable lignin-based water-soluble polymer flocculant into the stone powder slurry to achieve flocculation and precipitation of the stone powder;

[0023] The ultrasonic stirring flocculation device utilizes high-frequency vibration of ultrasonic waves to achieve irregular vibration stirring of the stone powder after adding the degradable lignin-based water-soluble polymer flocculant, thereby accelerating the flocculation process of the stone powder;

[0024] The vacuum adsorption filtration device uses vacuum negative pressure to remove the clean water after the stone powder flocculation and precipitation;

[0025] The electromagnetic wave energy directional excitation device utilizes the principle of dipole rearrangement in an electromagnetic field to achieve molecular oscillation at a speed of up to hundreds of millions of times per second, further stimulating the molecular activity in stone powder and diagenetic agents, accelerating the polymerization and hardening process of stone powder under the action of diagenetic agents, and completely degrading degradable lignin-based water-soluble polymers.

[0026] Preferably, the stone powder flocculation and precipitation device comprises: a degradable lignin-based water-soluble polymer quick-setting agent feeder (1), a stone powder storage bin (15), a wet sand making stone powder feeding device (2) and a clean water outlet (16);

[0027] The ultrasonic stirring flocculation device comprises an ultrasonic vibrator (12), an ultrasonic vibration generator (7) and a control panel (6); the ultrasonic vibrator is a core component for generating ultrasonic waves, is made of piezoelectric ceramic material, and can convert electrical energy into ultrasonic vibrations; the ultrasonic vibration generator generates a high-frequency electrical signal and transmits it to the ultrasonic vibrator, thereby driving the ultrasonic vibrator to generate ultrasonic vibrations; the control panel is used to set the working parameters of the ultrasonic stirring flocculation device, such as stirring time, stirring rate, etc.

[0028] The vacuum adsorption filtration device comprises a purification filter (14), a vacuum adsorption conduit (13), a vacuum dehydration storage device (10) and a high-power vacuum pump (11); the purification filter is composed of a filter screen with a pore size of less than 0.15 mm, and is used to filter wastewater generated after stone powder flocculation and powder particles that are not agglomerated; the vacuum adsorption conduit is used to connect the purification filter and the vacuum dehydration storage device; the vacuum dehydration storage device is used to collect liquid discharged by vacuum dehydration; the high-power vacuum pump is a high-power vacuum pump with a power in the range of 100W to 500W and capable of providing a negative pressure of 0 to 1.0MPa;

[0029] The electromagnetic wave energy directional excitation device comprises an electromagnetic wave energy generator (4) and an electromagnetic wave energy directional transmission device (5); the electromagnetic wave energy generator generates high-frequency electromagnetic waves through an oscillator and then converts them into microwave energy; the electromagnetic wave energy directional transmission device is a part that controls the transmission of microwave energy, specifically comprising components such as waveguides, transmission lines or microwave antennas, and can effectively transmit microwave energy to stone powder under the action of a diagenetic agent.

[0030] The high-frequency vibration screening device includes square hole sieves 7 with apertures of 20 mm, 10 mm, 4.75 mm, 2.36 mm, 1.18 mm, 600 μm, 300 μm and 150 μm, which are stacked from high to low. A high-frequency vibration tray and a high-frequency vibration base are installed at the bottom, which can enable the high-frequency vibration screening device to perform screening at a frequency of 2000 to 5000 times per minute.

[0031] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The performance of stone powder recycled aggregate is the same as that of machine-made aggregate: the present invention utilizes a diagenetic agent to fully stimulate the activity of stone powder, uses stone powder as a gelling material, and combines an electromagnetic wave energy directional excitation device to accelerate the movement rate of the diagenetic agent molecules, so that the stone powder is directly condensed and hardened into agglomerates in wastewater. The stone powder recycled aggregate prepared by the present invention is condensed and hardened during the agglomeration process, and its particle morphology is better than that of traditional machine-made aggregates, and its firmness is ≤8.0%, and the single-stage maximum crushing index is ≤25%;

[0033] 2. Realize the synchronous sand making of stone powder in the wet sand making process: The stone powder regeneration aggregate made by the present invention is directly carried out in the wastewater generated in the wet sand making process, without the need to wash and dry the stone powder in advance; the wet sand making stone powder aggregate making device of the present invention realizes the synchronous sand making of stone powder in the wet sand making process;

[0034] 3. Solve the problem of large amounts of flocculants remaining in stone powder: The present invention uses a degradable lignin-based water-soluble polymer flocculant to replace the commonly used polyacrylamide flocculant, which is rapidly degraded under the action of the degradation components of the flocculant, eliminating the influence of the flocculant on the structural properties of the subsequent stone powder-made recycled aggregate. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a schematic diagram of a device for preparing recycled aggregate by wet sand and stone powder according to an embodiment of the present invention. DETAILED DESCRIPTION

[0036] Embodiments of the present invention are described below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but are not to be construed as limiting the present invention.

[0037] like Figure 1 As shown, the device used in the method for preparing recycled aggregate by wet sand and stone powder in the embodiment of the present invention includes: a stone powder flocculation and sedimentation device, an ultrasonic stirring flocculation device, a vacuum adsorption and filtration device, an electromagnetic wave energy directional excitation device and a high-frequency vibration screening device.

[0038] The stone powder flocculation and precipitation device comprises: a degradable lignin-based water-soluble polymer quick-setting agent feeder (1), a stone powder storage bin (15), a wet sand making stone powder feeding device (2) and a clean water outlet (16);

[0039] The ultrasonic stirring flocculation device comprises an ultrasonic vibrator (12) and a control panel (6);

[0040] The vacuum adsorption filtration device comprises a purification filter (14), a vacuum adsorption conduit (13), a vacuum dehydration storage device (10) and a high-power vacuum pump (11);

[0041] The electromagnetic wave energy directional excitation device comprises an electromagnetic wave energy generator (4) and an electromagnetic wave energy directional transmission device (5); an electromagnetic wave energy directional excitation device protection device (3) is arranged outside the electromagnetic wave energy directional excitation device;

[0042] The high-frequency vibration screening device comprises square hole sieves 7 with apertures of 20 mm, 10 mm, 4.75 mm, 2.36 mm, 1.18 mm, 600 μm, 300 μm and 150 μm, which are stacked from high to low. A high-frequency vibration tray (8) and a high-frequency vibration base (9) are installed at the bottom, which enable the high-frequency vibration screening device to perform screening at a frequency of 2000 to 5000 times per minute.

[0043] The above-mentioned degradable lignin-based water-soluble polymer flocculant is prepared by using lignin, acrylamide monomer and functional monomer, and by adding an initiator (for initiating polymerization reaction), a polymer dispersant (for adjusting the dispersibility of the reaction system to ensure the smooth progress of the reaction) and a cross-linking agent (for enhancing the degree of cross-linking between polymer molecules and improving the stability of the product).

[0044] Functional monomers include acrylic acid (AA), methyl methacrylate (MMA) and N-vinyl pyrrolidone (NVP).

[0045] The initiator can be potassium persulfate, sodium bisulfite, etc.

[0046] Polymer dispersants include high molecular weight dispersants, such as polyvinyl pyrrolidone (PVP), sodium polyacrylate, etc.; surfactant dispersants include anionic (such as sodium dodecyl sulfate), cationic (such as hexadecyltrimethylammonium bromide), non-ionic (such as polyoxyethylene sorbitan monolaurate); inorganic salt dispersants include phosphates, silicates and other inorganic salts that can be used as effective dispersants in some cases.

[0047] The crosslinking agent is selected from N,N'-methylenebisacrylamide (MBA), ethylene glycol dimethacrylate and the like.

[0048] The method for preparing the degradable lignin-based water-soluble polymer flocculant used in the embodiment of the present invention comprises the following steps:

[0049] 1. Raw materials:

[0050] Lignin, acrylamide (AM), functional monomers, crosslinking agents, initiators and polymer dispersants.

[0051] 2. Ratio:

[0052] Lignin: 46% of the total mass of lignin-based water-soluble polymer flocculant

[0053] Acrylamide (AM): accounts for 40% of the total mass of the lignin-based water-soluble polymer flocculant.

[0054] Functional monomer (acrylic acid AA): accounts for 10% of the total mass of the lignin-based water-soluble polymer flocculant.

[0055] Cross-linking agent (N,N'-methylenebisacrylamide MBA): accounts for 3% of the total mass of the lignin-based water-soluble polymer flocculant.

[0056] Initiator (sodium bisulfite): 0.5% of the total mass of the lignin-based water-soluble polymer flocculant.

[0057] Dispersant (polyvinyl pyrrolidone PVP): accounts for 0.5% of the total mass of the lignin-based water-soluble polymer flocculant.

[0058] 3. Methods and steps:

[0059] Lignin purification: The enzymatic lignin is purified through steps such as dissolution, pH adjustment, filtration, and drying to remove impurities and improve its purity, which shall not be less than 90%.

[0060] First reaction: under nitrogen protection or inert gas atmosphere, add purified enzymatic lignin and solvent (such as water or organic solvent) to the reactor, and add initiator at the same time. At an ambient temperature of 60°C-90°C, stir the solution at a stirring rate of 200-600 rpm to decompose the initiator to generate free radicals, thereby initiating a polymerization reaction between lignin and acrylamide monomers to form a preliminary lignin-acrylamide grafted polymer.

[0061] Second reaction: After the first reaction is completed, a polymer dispersant (to adjust the dispersibility of the reaction system and prevent particle aggregation) and a selected cross-linking agent (such as N,N'-methylenebisacrylamide to enhance the degree of cross-linking between polymer molecules) are added to the reaction system to carry out a second stage of polymerization reaction, so that these monomers further react with the initially formed grafted polymer to form a lignin-based water-soluble polymer with a variety of functional structural units.

[0062] Purification: The product obtained from the second reaction is purified. First, the polymer is precipitated from the solution by soaking and precipitation, and then washed with water several times to remove impurities such as residual unreacted monomers, oligomers and solvents. After that, the washed polymer is dried to remove moisture. The dried polymer is crushed and sieved to obtain a lignin-based water-soluble polymer product.

[0063] 4. Product structure

[0064] The product exhibits high molecular weight (2000-3500 kD) and has a complex network structure or branched structure. Since the preparation process of lignin-based water-soluble polymer flocculants involves complex chemical reactions and interactions of multiple raw materials, the molecular weight of the product structure is usually difficult to accurately control.

[0065] Example 1

[0066] A method for preparing recycled aggregate by wet sand and stone powder production comprises the following steps:

[0067] Step 1: inject the wet sand making sand washing wastewater containing 10000 mg of stone powder into the stone powder storage bin of the stone powder flocculation precipitation device through the wet sand making stone powder feeding device, and then add 10 mg of degradable lignin-based water-soluble polymer flocculant through the feeder for flocculation precipitation. After the precipitation is complete, the upper clear water is discharged through the clean water outlet;

[0068] Step 2: Turn on the ultrasonic stirring flocculation device, set the stirring time of the device to 60s and the ultrasonic stirring power to 1500W, so as to accelerate the coagulation of the wet-process washed sand and stone powder under the action of the degradable lignin-based water-soluble polymer flocculant;

[0069] Step 3: After the stone powder is condensed into a mass in water, sodium dialkyl sulfate (SDS) is added until its molar concentration in the solution is 0.024 mol / L; a sodium silicate (Na2O·nSiO2) solution with a modulus of 1.2 and a solid content of 45% and a specific surface area of ​​600m 2 / kg, an activity index of 130%, ultrafine slag powder with a fineness D90 of less than 10μm and water in a mass ratio of 3:0.5:8 to obtain a stone powder inorganic cementing component, and continue stirring until the stone powder inorganic cementing component is uniformly adsorbed on the surface of the stone powder agglomerated particles; turn off the ultrasonic stirring flocculation device, add a flocculant degradation component with a chemical formula of NaOH to ensure that its molar concentration in the solution is 3mol / L, and form a recycled aggregate with a certain strength;

[0070] Step 4: Filter out the wastewater outside the agglomerated aggregate through a vacuum adsorption filtration device at a vacuum degree of 0.06MPa, turn on the electromagnetic wave energy directional excitation device, set the frequency of the device to 2450MHz, the wavelength to 0.122m, and the output power to 600W, so as to accelerate the evaporation of water inside the aggregate, and further promote the coagulation and hardening of the stone powder recycled aggregate to meet the performance requirements; turn on the high-frequency vibration screening device to screen the recycled aggregate into graded aggregates of 0.15mm-0.30mm, 0.30mm-0.60mm, 0.60mm-1.18mm, 1.18mm-2.36mm, 2.36mm-4.75mm, 5mm-10mm and 10mm-20mm, and complete the preparation of wet-process machine-made sand and stone powder recycled aggregate.

[0071] The properties of the recycled aggregate prepared by wet process machine-made sand and gravel powder are shown in Table 1.

[0072] Table 1 Performance of recycled aggregate made from wet-process machine-made sand and gravel powder in Example 1

[0073] project Firmness / % Crushing index / % Example 1 6.2% (Class II) 22.6% (Class II)

[0074] Example 2

[0075] A method for preparing recycled aggregate by wet sand and stone powder production comprises the following steps:

[0076] Step 1: inject the wet sand making sand washing wastewater into the stone powder storage bin of the stone powder flocculation sedimentation device through the wet sand making stone powder feeding device, and then add the degradable lignin-based water-soluble polymer flocculant through the feeder for flocculation and sedimentation. After the sedimentation is complete, the upper clear water is discharged through the clean water outlet;

[0077] Step 2: Turn on the ultrasonic stirring flocculation device, set the stirring time of the device to 60s and the ultrasonic stirring power to 1500W, so as to accelerate the coagulation of the wet-process washed sand and stone powder under the action of the degradable lignin-based water-soluble polymer flocculant;

[0078] Step 3: After the stone powder is condensed into a mass in water, sodium dialkyl sulfate (SDS) is added until its molar concentration in the solution is 0.052 mol / L; a sodium silicate (Na2O·nSiO2) solution with a modulus of 1.2 and a solid content of 45% and a specific surface area of ​​600m 2 / kg, an activity index of 130%, ultrafine slag powder with a fineness D90 of less than 10μm and water in a mass ratio of 3:0.5:8 to obtain a stone powder inorganic cementing component, and continue stirring until the stone powder inorganic cementing component is uniformly adsorbed on the surface of the stone powder agglomerated particles; turn off the ultrasonic stirring flocculation device, add a flocculant degradation component with a chemical formula of NaOH to ensure that its molar concentration in the solution is 5mol / L, and form a recycled aggregate with a certain strength;

[0079] Step 4: Filter out the wastewater outside the agglomerated aggregate through a vacuum adsorption filtration device at a vacuum degree of 0.08MPa, turn on the electromagnetic wave energy directional excitation device, set the frequency of the device to 2450MHz, the wavelength to 0.122m, and the output power to 600W, so as to accelerate the evaporation of water inside the aggregate, and further promote the coagulation and hardening of the stone powder recycled aggregate to meet the performance requirements; turn on the high-frequency vibration screening device to screen the recycled aggregate into graded aggregates of 0.15mm-0.30mm, 0.30mm-0.60mm, 0.60mm-1.18mm, 1.18mm-2.36mm, 2.36mm-4.75mm, 5mm-10mm and 10mm-20mm, and complete the preparation of wet-process machine-made sand and stone powder recycled aggregate.

[0080] The properties of the recycled aggregate prepared by wet process machine-made sand and gravel powder are shown in Table 2.

[0081] Table 2 Performance of recycled aggregate made from wet-process machine-made sand and gravel powder in Example 2

[0082] project Firmness / % Crushing index / % Example 2 4.3% (Class I) 20.8% (Class II)

[0083] Example 3

[0084] A method for preparing recycled aggregate by wet sand and stone powder production comprises the following steps:

[0085] Step 1: inject the wet sand making sand washing wastewater into the stone powder storage bin of the stone powder flocculation sedimentation device through the wet sand making stone powder feeding device, and then add the degradable lignin-based water-soluble polymer flocculant through the feeder for flocculation and sedimentation. After the sedimentation is complete, the upper clear water is discharged through the clean water outlet;

[0086] Step 2: Turn on the ultrasonic stirring flocculation device, set the stirring time of the device to 60s and the ultrasonic stirring power to 1500W, so as to accelerate the coagulation of the wet-process washed sand and stone powder under the action of the degradable lignin-based water-soluble polymer flocculant;

[0087] Step 3: After the stone powder is condensed into a mass in water, sodium dialkyl sulfate (SDS) is added until its molar concentration in the solution is 0.086 mol / L; a sodium silicate (Na2O·nSiO2) solution with a modulus of 1.2 and a solid content of 45% and a specific surface area of ​​600m 2 / kg, an activity index of 130%, ultrafine slag powder with a fineness D90 of less than 10μm and water in a mass ratio of 3:0.5:8 to obtain a stone powder inorganic cementing component, and continue stirring until the stone powder inorganic cementing component is uniformly adsorbed on the surface of the stone powder agglomerated particles; turn off the ultrasonic stirring flocculation device, add a flocculant degradation component with a chemical formula of NaOH to ensure that its molar concentration in the solution is 5mol / L, and form a recycled aggregate with a certain strength;

[0088] Step 4: Filter out the wastewater outside the agglomerated aggregate through a vacuum adsorption filtration device at a vacuum degree of 0.08MPa, turn on the electromagnetic wave energy directional excitation device, set the frequency of the device to 2450MHz, the wavelength to 0.122m, and the output power to 900W, so as to accelerate the evaporation of water inside the aggregate, and further promote the coagulation and hardening of the stone powder recycled aggregate to meet the performance requirements; turn on the high-frequency vibration screening device to screen the recycled aggregate into graded aggregates of 0.15mm-0.30mm, 0.30mm-0.60mm, 0.60mm-1.18mm, 1.18mm-2.36mm, 2.36mm-4.75mm, 5mm-10mm and 10mm-20mm, and complete the preparation of wet-process machine-made sand and stone powder recycled aggregate.

[0089] The properties of the recycled aggregate prepared by wet process machine-made sand and gravel powder are shown in Table 3.

[0090] Table 3 Performance of recycled aggregate made from wet-process machine-made sand and gravel powder in Example 3

[0091] project Firmness / % Crushing index / % Example 3 4.0% (Class I) 19.6% (Class I)

[0092] Comparative Example 1

[0093] When no flocculant degradation component is added, the wet method of preparing recycled aggregate from sand and stone powder includes the following steps:

[0094] Step 1: inject the wet sand making sand washing wastewater into the stone powder storage bin of the stone powder flocculation sedimentation device through the wet sand making stone powder feeding device, and then add the degradable lignin-based water-soluble polymer flocculant through the feeder for flocculation and sedimentation. After the sedimentation is complete, the upper clear water is discharged through the clean water outlet;

[0095] Step 2: Turn on the ultrasonic stirring flocculation device, set the stirring time of the device to 60s and the ultrasonic stirring power to 1500W, so as to accelerate the coagulation of the wet-process washed sand and stone powder under the action of the degradable lignin-based water-soluble polymer flocculant;

[0096] Step 3: After the stone powder is condensed into a mass in water, add 3% of sodium dialkyl sulfate (SDS) solution with a molar concentration of 0.086 mol / L, a sodium silicate (Na2O·nSiO2) solution with a modulus of 1.5 and a solid content of 40%, and a specific surface area of ​​800 m 2 / kg, an activity index of 150%, ultrafine slag powder with a fineness D90 of less than 10μm and water in a mass ratio of 5:1:10 to obtain a stone powder inorganic cementing component, and continue stirring until the stone powder inorganic cementing component is uniformly adsorbed on the surface of the stone powder agglomerate particles; turn on the electromagnetic wave energy directional excitation device to accelerate the movement rate of the diagenetic agent molecules inside the recycled aggregate to form a recycled aggregate with a certain strength;

[0097] Step 4: Filter out the wastewater outside the agglomerated aggregate through a vacuum adsorption filtration device at a vacuum degree of 0.08MPa, turn on the electromagnetic wave energy directional excitation device, set the frequency of the device to 2450MHz, the wavelength to 0.122m, and the output power to 900W, so as to accelerate the evaporation of water inside the aggregate, and further promote the coagulation and hardening of the stone powder recycled aggregate to meet the performance requirements; turn on the high-frequency vibration screening device to screen the recycled aggregate into graded aggregates of 0.15mm-0.30mm, 0.30mm-0.60mm, 0.60mm-1.18mm, 1.18mm-2.36mm, 2.36mm-4.75mm, 5mm-10mm and 10mm-20mm, and complete the preparation of wet-process machine-made sand and stone powder recycled aggregate.

[0098] Table 4 Comparative Example 1 Performance of recycled aggregate made from wet-process machine-made sand and gravel powder

[0099] project Firmness / % Crushing index / % Comparative Example 1 23.9% (not up to standard) 52.3% (not up to standard)

[0100] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A wet sand and stone powder active diagenetic agent, characterized in that: It contains 5-10 parts by weight of a flocculant degradation component, 1-3 parts by weight of a surfactant component, and 15-20 parts by weight of a stone powder inorganic cementing component; The flocculant degradation component is a NaOH or KOH solution with a molar concentration of 2 mol / L to 5 mol / L; The surface active component is sodium dodecyl sulfate or octylphenol polyoxyethylene ether with a molar concentration of 0.01 mol / L to 0.1 mol / L; The stone powder inorganic cementing component is sodium silicate with a modulus of 1.0 to 1.5 and a specific surface area of ​​600m 2 / kg, activity index ≥120%, ultrafine slag powder with a fineness D90 below 10μm and water in a mass ratio of (3-5): (0.5-1): (8-10) to obtain a solution.

2. Application of the wet-process sand and stone powder activity-stimulating diagenetic agent according to claim 1 in the preparation of recycled aggregates by wet-process sand and stone powder.

3. A method for preparing recycled aggregate by wet sand and stone powder production, characterized in that: The specific steps include: Step 1: Add a degradable lignin-based water-soluble flocculant to the stone powder slurry produced by wet sand making for flocculation and precipitation, and drain the upper clear water after the precipitation is complete; Step 2: using an ultrasonic stirring and flocculation device to perform ultrasonic stirring and flocculation on the stone powder obtained by wet sand making; Step 3, adding the stone powder activity activating diagenetic agent described in claim 1 to the flocculated stone powder to prepare a primary formed recycled aggregate; Step 4: Filter the initially formed recycled aggregate from the diagenetic agent, use the electromagnetic wave energy directional excitation device again to accelerate the hardening of the aggregate, and obtain recycled aggregates of different particle sizes after screening.

4. The method for preparing recycled aggregate by wet sand and stone powder production according to claim 3, characterized in that: The degradable lignin-based water-soluble flocculant is prepared by grafting lignin oligomers with D-lysine through a Mannich reaction.

5. The method for preparing recycled aggregate by wet sand and stone powder production according to claim 3, characterized in that: In step 2, the stirring time of ultrasonic stirring flocculation is 30s-60s, and the ultrasonic stirring power is 1000W-1500W.

6. The method for preparing recycled aggregate by wet sand and stone powder production according to claim 3, characterized in that: In step three, a diagenetic agent accounting for 5%-10% of the total amount of stone powder is added.

7. The method for preparing recycled aggregate by wet sand and stone powder production according to claim 3, characterized in that: The working parameters of the directional excitation of electromagnetic wave energy in step four; the screening uses a high-frequency vibration screening device to screen the hardened recycled aggregate into recycled aggregates with different particle sizes of 0.15mm~0.30mm, 0.30mm~0.60mm, 0.60mm~1.18mm, 1.18mm~2.36mm, 2.36mm~4.75mm, 5.00mm~10.00mm and 10.00mm~20.00mm.

8. The method for preparing recycled aggregate by wet sand and stone powder production according to claim 3, characterized in that: The device for preparing recycled aggregate by wet sand and stone powder comprises: a stone powder flocculation and sedimentation device, an ultrasonic stirring flocculation device, a vacuum adsorption and filtration device, an electromagnetic wave energy directional excitation device and a high-frequency vibration screening device.

9. The method for preparing recycled aggregate by wet sand and stone powder production according to claim 8, characterized in that: The stone powder flocculation and precipitation device comprises: a degradable lignin-based water-soluble polymer quick-setting agent feeder (1), a stone powder storage bin (15), a wet sand making stone powder feeding device (2) and a clean water outlet (16); The ultrasonic stirring flocculation device comprises an ultrasonic vibrator (12), an ultrasonic vibration generator (7) and a control panel (6); The vacuum adsorption filtration device comprises a purification filter (14), a vacuum adsorption conduit (13), a vacuum dehydration storage device (10) and a high-power vacuum pump (11); The electromagnetic wave energy directional excitation device comprises an electromagnetic wave energy generator (4) and an electromagnetic wave energy directional transmission device (5).

10. Recycled aggregate prepared by the method according to any one of claims 3 to 9.

Citation Information

Patent Citations

  • Method for preparing blast furnace slag modified siliceous stone powder cementing materials with different properties by controlling water loss rate

    CN114031317A

  • Method for controlling residual amount of flocculating agent in washing machine-made sand

    CN114804405A

  • Flocculant composition and water treatment method

    JP2019072701A

  • Method for Artificial Stone Figures Using RecycledStone Powder

    KR1020030036459A

  • Method for grafting lignin, polymerizates produced according to the method and the utilization thereof

    US6593460B1